Effects of Composite Material Layers on the Mechanical Properties for Partial Foot Prosthetic Socket - Abbas, S. M. (Al-Nahrain Journal for Engineering Sciences, 2018)
In this work, nine types of laminated composite materials used for experimental study to investigate the tensile and fatigue properties of partial foot prosthetic socket which fabricated by using vacuum pressure system . The composite material matrix were Lamination 80:20and reinforced with nine types of laminations (perlon, n-glass, fiber glass and carbon) by variation of thickness according to lamination. Results show that the mechanical properties were improved by increasing the two layers of carbon fiber, fiber glass and n-glass layers instead of zero layer with six layers of perlon lead to the increased in(yield strength ?y, ultimate tensile strength ?ult and modules of elasticity E with (71% ,76% and 58%) respectively for carbon fiber, (20% , 19% and 40%) for fiber glass and ( 22% , 5.5% and 29% ) for n-glass. Results show that (3perlon+2carbon fiber+3perlon) gives the best value of mechanical properties and has higher Endurance limit stresses (?e) which increase lifetime for the patient . It is recommend to use this type of lamination for the layup partial foot prosthetic socket because it meets the demand lamination layers for acceptable mechanical properties and its minimizing the cost of socket lamination to suitable costing value.